Dari Surau ke Madrasah : Modernisasi Pendidikan Islam Di Minangkabau 1900-1930 M - Satria, Rengga (State Islamic Institute of Madura, 2019)
This study concludes that the modernization movement of Islamic education that occurred in Minangkabau in the period 1900-1930 caused the